Pengaruh Kualitas Pelayanan, Store Atmosphere, dan Strategi Proaktif di CV MM Acing Jaya Pangkalpinang - Maharani, Aulia Hari; Ramadhani, Siska; Irwana, Natasia; Noviyanti, Indah (FEB Universitas Maritim Semarang, 2025)
This study aims to evaluate the extent to which service quality, store atmosphere, and the implementation of proactive strategies contribute to business strategy at CV MM Acing Jaya located in Pangkalpinang. This study uses a quantitative approach with data collection techniques through distributing questionnaires to 71 respondents consisting of customers and business partners of the company. Multiple linear regression analysis was used to test the research hypothesis consisting of three independent variables (service quality, store atmosphere, and proactive strategy) and one dependent variable (business strategy). The results showed that store atmosphere and proactive strategy had a positive and significant effect on business strategy, while service quality showed no significant effect. The findings suggest that the creation of a supportive store atmosphere and the implementation of responsive and innovative strategies are important factors in strengthening the competitiveness of ritel companies. This research provides a practical contribution for businesses in developing business strategies that are more adaptive and oriented to consumer needs.